Methodology for estimation of mean annual rate of exceedance of collapse of buildings under earthquake excitation - Kamatchi, P.; Sunil, J.C.; Kumar, K. Sathish (Journal of Structural Engineering, 2024)
State-of-art performance based requirement of seismic design of building requires that for life safety, probability of collapse in 50 years should not exceed 1%. In this paper, a methodology for estimation of mean annual rate of exceedance of collapse of buildings is demonstrated for two buildings B1 and B2. For B1 which is a three storey steel building frame two hazard risk levels (2% and 0.1% probability of exceedance in 50 years) and one site location (Bhuj) are considered. For B2, four different locations (Ahmedabad, Chennai, Mumbai and Banglore) and one seismic hazard risk level (2% probability of exceedance in 50 years) are considered. From the study, probability of collapse of B1 in 50 years for Bhuj site for an earthquake hazard risk of 2% probability of exceedance in 50 years is estimated to be 75%. Probability of collapse of B2 in 50 years for Ahmedabad, Chennai, Mumbai and Banglore are estimated to be 6.83%, 0.056%, 4.78% and 0.012% respectively. Further, this methodology brings out the spectral acceleration Sₐ(T1) which contributes maximum to the hazard which is also a useful design parameter. Methodology demonstrated in this paper is useful for estimation of probability of collapse of building for a given design life of structure.